2018
DOI: 10.1111/cns.13057
|View full text |Cite
|
Sign up to set email alerts
|

Impaired histaminergic neurotransmission in children with narcolepsy type 1

Abstract: Narcolepsy type 1 children had a higher CSF HA level together with a lower t-MeHA level leading to a significant decrease in the t-MeHA/HA ratios. These results suggest a decreased HA turnover and an impairment of histaminergic neurotransmission in narcoleptic children and support the use of a histaminergic therapy in the treatment against narcolepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…Regardless, our data support the view that at least on the C57Bl/6J background, congenital orexin peptide deficiency is sufficient to increase histamine neuron number in adulthood. This result may represent a homeostatic compensation for the loss of orexin peptides, or for an impairment of histaminergic neurotransmission, recently described in narcoleptic children close to disease onset ( Franco et al, 2019 ).…”
Section: Discussionmentioning
confidence: 81%
“…Regardless, our data support the view that at least on the C57Bl/6J background, congenital orexin peptide deficiency is sufficient to increase histamine neuron number in adulthood. This result may represent a homeostatic compensation for the loss of orexin peptides, or for an impairment of histaminergic neurotransmission, recently described in narcoleptic children close to disease onset ( Franco et al, 2019 ).…”
Section: Discussionmentioning
confidence: 81%
“…However, in the few patients reported in our study, no differences were found in CSF hypocretin‐1 levels between children and adults. We recently reported an impairment in histamine neurotransmission, another brain wake‐promoting system, in children with NT1, 41 which was not found in adults 42 . Histaminergic neurons could be also involved as studies in animal models have suggested that lack of either hypocretin or histamine could lead to a mild obesity 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Since brain histamine has a strong impact on the vigilant state, the involvement of the histaminergic system in narcolepsy has been extensively studied. Several reports showed lower histamine levels in the CSF of narcolepsy patients (Kanbayashi et al, 2009; Nishino et al, 2009) and a recent study indicated the involvement of impaired histaminergic neurotransmission in narcoleptic children (Franco et al, 2019). However, the association of CSF histamine levels with narcolepsy was not confirmed in other studies (Croyal et al, 2011; Dauvilliers et al, 2012), indicating that the causative role of histaminergic dysfunction in narcolepsy is still inconclusive.…”
Section: Box 1: Neuronal Histaminergic System and Related Diseasesmentioning
confidence: 99%
“…n K i value of histamine to 0.4-nM [ 125 I]-iodoaminopotentidine in the homogenates of rat H 2 R transfected Sf9 cells (Beukers et al, 1997). o K i value of histamine to 2-nM [ 3 H]-tiotidine in the homogenates of guinea pig lung parenchyma (Foreman et al, 1985). ; Oda et al (2000).…”
Section: Histamine H 3 Receptormentioning
confidence: 99%